2021
DOI: 10.1093/ofid/ofab005
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Seroconversion and Viral Clearance in Patients Hospitalized With COVID-19: Viral Load Predicts Antibody Response

Abstract: Objectives The interdependencies of viral replication and the host immune response in patients with COVID-19 remain to be defined. We investigated the viral determinants of antibody response, the predictors of non-seroconversion, and the role of antibodies on viral dynamics. Methods Prospective study in patients hospitalized with microbiologically confirmed COVID-19 by real-time polymerase-chain-reaction (RT-PCR). Serial naso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 23 publications
6
52
0
Order By: Relevance
“…Most of immune competent COVID-19 patients show a seroconversion 8-14 days after diagnosis. 9 In line with a previous reporting, 7 our patients showed no IgM antibody response evaluated by rapid immunochromatographic assay and absent/inadequate response in terms of SARS-CoV-2 anti-spike IgG production (range 0.01 -0.05 UI/ml) 40-74 days after initial symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…Most of immune competent COVID-19 patients show a seroconversion 8-14 days after diagnosis. 9 In line with a previous reporting, 7 our patients showed no IgM antibody response evaluated by rapid immunochromatographic assay and absent/inadequate response in terms of SARS-CoV-2 anti-spike IgG production (range 0.01 -0.05 UI/ml) 40-74 days after initial symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…A prospective study was conducted in a cohort of patients hospitalized for microbiologically-confirmed COVID-19 with a positive SARS-CoV-2 RNA test in a nasopharyngeal sample in the first wave, who were longitudinally followed-up during 12 months; details of the cohort with preliminary, short-term results are provided elsewhere [ 6 , 10 ]. The study was approved by the Ethical Committee of the Hospital General Universitario de Elche (Spain).…”
Section: Methodsmentioning
confidence: 99%
“…The dynamics of humoral immune response determine the speed of viral elimination. Faster viral clearance is associated with earlier antibody responses—where low initial SARS-CoV-2 RNA was detected in patients who did not have S IgG—suggesting that induction of adaptive humoral response may be dependent on the strength of viral replication [ 54 ]. Interestingly, men have higher antibody titres compared to women in the acute phase [ 27 ].…”
Section: Production Of Neutralising Antibodiesmentioning
confidence: 99%
“…With regards to seroconversion, patients who did not seroconvert or had reduced or delayed seroconversion had the lowest viral loads [ 54 ] or were asymptomatic [ 27 ] (Table 1 ). Long et al [ 29 ] reported that seroconversion for IgG and IgM occurred concurrently or sequentially, and that the titres for both reached a plateau within 6 days after seroconversion.…”
Section: Production Of Neutralising Antibodiesmentioning
confidence: 99%